Filamentous Fungi for Bioremediation of Oily Effluents of a Local Ghee Industry in Pakistan: An Environmental Perception - Hajra Khalil; Samina Sarwar; Sobia Ilyas; Muhammad Hanif; Amina Abrar; Mobina Ulfat (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Mycoremediation is emerging as a potential approach for eco-friendly, cost-effective, and the most natural attenuation due to the biodegradation of polluted effluents from oil effluents which affect human health and the ecosystem. This work dealt with the analyses of the biodegradation capability of some potential indigenous fungal isolates viz., Aspergillus flavus, Aspergillus niger, and Rhizopus stolonifer, against oil effluents collected from a local ghee industry in Pakistan. Percentage reduction potential in different parameters i.e., pH, Electrical Conductivity (EC), Total Suspended Solids (TSS), Total Dissolved Solids (TDS), Biological Oxygen Demand (BOD), and Chemical Oxygen Demand (COD), confirmed that these fungi had the potential to degrade oily effluents. Aspergillus niger showed the highest reduction potential, while A. flavus and R. stolonifer had the least reduction potential to treat oil pollution. This indicates the potential of these identified fungi as biosorbents for removing high oil contents from industrial and wastewater discharge.